Spectrophotometric Determination of Chloramphenicol by Oxidative Coupling Reaction with Naphthalene-1, 5-Diamine in the Presence of Potassium Iodate - Kameran Shukur Hussein; Abdul Majeed Khorsheed Ahmed; Fatimah Yunadi Mohammed (Tikrit Journal of Pure Science)
A simple, accurate, and sensitive method for the spectrophotometric determination of Chloramphenicol (CAP) in pharmaceutical preparations. The method is based on the oxidative coupling reaction of Chloramphenicol after reducing the nitro group in the drug into an amino group with Naphthalene-1,5-diamine as a reagent in the presence of potassium Iodate as an oxidizing agent formed violet dye that is soluble in water and have a maximum absorption at 568nm. Beer's law is obeyed in the concentration range of 6-27㎍.mL-1 with a molar absorptivity of 0.4805×104 L.mol-1.cm-1, and Sandell's sensitivity was 0.061㎍.cm-2, respectively. The correlation coefficient was 0.9994, with recovery average % was 100.05. Detection limit (D.L) and quantitative limit (Q.L) were 0.241㎍.ml- 1 and 0.804 ㎍.ml -1. The product was stable for 70 minutes with relative error (RE) % of -0.12 to -0.22 and a relative standard deviation (RSD) % of 0.476 to 0.362. The method was successfully applied to the analysis of Chloramphenicol in pharmaceutical preparations (Eye drop).